Idiomatska beseda ali frazeološka enota - Kržišnik, Erika (Slavistična revija, 2010)
Defining the limit that is linguistically substainted in the article is to some extand connected to the theoretical approach - the author discusses the idom- and phras- approaches - which, in turn, depends on the type of language that provides the material for examination. The so-called bottom limit of a phraseological unit will be determined by the material from Slovene as one of Slavic languages, in which boudaries or, rather, endings of the words are mailnly marked by variation of form, i.e., morphological and word-formational variation.
Keywords: frazemi; frazeologija; idiomatika; phraseology; Slovene; slovenščina